Low dose-eplerenone treatment decreases aortic stiffness in patients with resistant hypertension - Kalizki, Tatjana; Schmidt, Bernhard Magnus Wilhelm; Raff, Ulrike; Reinold, Annemarie; Schwarz, Thomas K.; Schneider, Markus P.; Schmieder, Roland; Schneider, Andreas (Journal of Clinical Hypertension, 2017)
Vascular damage is aggravated in animal models of hypertension with mineralocorticoid (MR) excess and in hypertensive patients with primary hyperaldosteronism. MR antagonism has shown to provide effective blood pressure (BP)-control in patients with treatment resistant hypertension (TRH), but the concurrent effects on the vasculature have not been examined. In a randomized, double-blinded, placebo-controlled parallel-group study, 51 patients with TRH received either eplerenone 50 mg or placebo for 6 months together with additional antihypertensives titrated to achieve a BP target of <140/90 mm Hg. Pulse wave velocity (PWV), augmentation index (AIx), augmentation pressure (AP), AP normalized to a heart rate of 75/min (AP@HR75), renal resistive index (RRI), intima-media thickness (IMT) and urinary albumin excretion rate (UAER) were assessed before and after treatment. PWV was reduced only with eplerenone (from 11.3±3.6 to 9.8±2.6 m/s, P?.001), but not with placebo (10.3±2.0 to 10.1±1.8 m/s, P=.60), despite similar reductions in BP (-35±20/-15±11 mm Hg vs -30±19/-13±7 mm Hg, n.s.). Further, reductions in AP and AP@HR75 were greater with eplerenone, while changes in AIx, RRI, IMT and UAER were similar. Our data show that eplerenone beneficially affects markers of arterial stiffness and wave reflection in patients with TRH, independently of BP lowering. These data add to the evidence that MR antagonism should be the preferred treatment option in TRH.
EVALuna2:3944